PERLINDUNGAN HUKUM BAGI INVESTOR SAHAM TERHADAP TERJADINYA FORCED DELISTING EMITEN DALAM KEGIATAN PASAR MODAL - , Markus Tampubolon, Dr.Sulistiowati,S.H.,M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to deepen knowledge and understanding of the protection provided by the hukm to investors due to the forced delisting of shares as well as to determine the constraints and solutions that can be provided to protect investors from losses forced delisting issuers . This study empirical jurisdiction, the research and analyzing secondary data which is followed by research and analyzing primary data. Qualitative analysis method is used to both secondary data and primary data, which is done by gathering and selecting secondary data from field studies to and connected with the theory obtained from the literature that can be obtained answers to the problems. Furthermore, the results presented descriptively. The results obtained indicate that there is still a lack of legal protection seen in the lack of net assets included in board development , low penalties against issuers , until the suspension is too long a period of two years , there is no obligation to buy shares that have been bought by investors . Assistance of law enforcement dam firmness of BEI and FSA still insufficient to protect investors . Underwriter as underwriters have added responsibility to ensure liquidity of their issuers . Constraints faced by the BEI is need for revision of the regulations FSA to increasing market liquidity and require additional public accountant to audit listed companies . FSA requires new members to carry out the task of FSA to oversee and investigate issuers on the exchange . Constraint is the lack of issuer disclosure principles and the principles of good corporate governance in business . Give rewards for companies that discipline and achievement as a moral booster issuers . Investors also should begin to increase knowledge in investing in the stock market by following school capital markets that are required and to learn from the investor broker .